MORALNI ASPEKT DOPINGA - Višeslav Krsmanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Expansion of top, competitive sports in last few decades has reached the global proportions and significance. Political, economic and cultural aspects of sports make it a very influental social phenomenon and value but on the other hand the limits of human capabilities and strong sport competition presents the basic limitations on the road that leads to the top of world class sport achievements, recognitions, awards, fame and personal fortune. Records, victories and achievements, prestige and benefits (on the national level), wear out fisical, psihological and moral aspect of every athlete putting them in temptetion of consuming unlegal medications during treaning or compiting acctivities. Legal (sport) standards and morality of athletes presents the foundation of defencive anti-doping strategy as a proactive method of fight against the usage of ileagal medicines in achieving better sport results. The basic moral principles of sport are justice and equiaty. They are an assumption of competition, but not the sport life outside of its bounderies. The research have shown that the usege of doping medicines is leaned on three motives: 1. toughness of treaning and lonelyness of athletes, 2. weak personal responsibilities, 3. moral predispositions and personal charakteristics od athletes. The concluion is that moral causes of doping usage are weaker than psihological (individual) and general social reasons. They are the part of decision of individuals and in the case of social moral crisis they could be an alibi for moral judgement. That doesn`t mean that value of morality is underestimated and neglected and that in social acctivities moral concenese and principles don`t have significant meaning. Predstavnici Ju